Variable or variate? A conundrum in pharmacometrics exposure-response models - Ana‐Marija Grisic; Karthik Venkatakrishnan; Jonathan French; Akash Khandelwal (Wiley, 2023)
Abstract Key elements of scientific writing-consistency and clarity-can be compromised in case of inaccurate use of methodological terms, especially in complex and multidisciplinary scientific fields. Such is the case in reports of pharmacometrics exposure-response analyses with the use of the terms univariate/multivariate and univariable/multivariable. This perspective outlines the issues in the use of these terms, clarifies their definitions, provides examples, and makes recommendations for authors, reviewers, and journals in the fields of clinical pharmacology and pharmacometrics.